Sensing of Letrozole Drug by Pure and Doped Boron Nitride Nanoclusters: Density Functional Theory Calculation - Afsoon Behmanesh; Farshid Salimi; Gholamreza Ebrahimzadeh-Rajaei (Pharmaceutical Sciences, 2023)
Background: Letrozole is a non-steroidal drug utilized as a treatment of hormone-sensitive breast cancer. It has been shown that letrozole has harmful side effects. Therefore, it seems necessary to design a letrozole drug sensor. In this work, we scrutinized the sensing properties of the B30N30, AlB29N30, and GaB29N30 nanoclusters toward the letrozole drug in various adsorption sites. Methods: Investigations were done using the density functional theory (DFT) calculation with the B3PW91/6-311G(d, p) level of theory. The time-dependent density functional theory (TD-DFT) calculations were used to investigate Ultraviolet-visible (UV-vis) spectrums with the same level of theory. Results: The adsorption energy of B30N30, AlB29N30, and GaB29N30 in the most stable complexes were calculated at -16.81, -34.62, and -27.41 kcal mol-1, respectively. The results obtained from the study of electronic properties showed a high sensitivity for the detection of letrozole in B30N30 compared to AlB29N30 and GaB29N30. The calculated recovery time for the B30N30 is 0.13 × 10-5 s, which indicates a very short recovery time. The UV-vis spectrums showed that the letrozole/B30N30 exhibits shift toward the higher wavelengths (red shift). Conclusion: Therefore, these results showed that the B30N30 is a good candidate for identifying letrozole. Further, B30N30 would be more effective than AlB29N30 and GaB29N30 due to the simple synthesis.